Histone posttranslational modifications and cell fate determination: lens induction requires the lysine acetyltransferases CBP and p300 - Wolf, Louise (Oxford University Press, 2013)
Lens induction is a classical embryologic model to study cell fate determination. It has been proposed earlier that specific changes in core histone modifications accompany the process of cell fate specification and determination. The lysine acetyltransferases CBP and p300 function as principal enzymes that modify core histones to facilitate specific gene expression. Herein, we performed conditional inactivation of both CBP and p300 in the ectodermal cells that give rise to the lens placode. Inactivation of both CBP and p300 resulted in the dramatic discontinuation of all aspects of lens specification and organogenesis, resulting in aphakia. The CBP/p300(−/−) ectodermal cells are viable and not prone to apoptosis. These cells showed reduced expression of Six3 and Sox2, while expression of Pax6 was not upregulated, indicating discontinuation of lens induction. Consequently, expression of αB- and αA-crystallins was not initiated. Mutant ectoderm exhibited markedly reduced levels of histone H3 K18 and K27 acetylation, subtly increased H3 K27me3 and unaltered overall levels of H3 K9ac and H3 K4me3. Our data demonstrate that CBP and p300 are required to establish lens cell-type identity during lens induction, and suggest that posttranslational histone modifications are integral to normal cell fate determination in the mammalian lens.